Metal coverage ratio of pipeline embolization device for treatment of unruptured aneurysms - Jour, Liang-Der (2016)
Background and purpose The metal coverage ratio (MCR) of a flow diverter influences the intra-aneurysmal hemodynamics; a high MCR will occlude an aneurysm early, while a low MCR may delay aneurysm occlusion. The true MCR of a pipeline embolization device (PED) could be lower due to oversize, device deformation, or aneurysm location. In this study deviation of the true MCR from the nominal MCR is assessed and whether their difference affects aneurysm occlusion rate is determined. Methods A total of 40 consecutive patients, each of them treated by one PED for their aneurysms at the internal carotid artery (ICA), were retrospectively analyzed. The DynaCT images of these deployed PEDs were used to determine their true dimensions and estimate three MCRs (local, mean, and nominal). These data were compared in two groups of patients who had different aneurysm outcomes at six months. Results The difference in the local MCR between two groups is small, but statistically significant (24.5% vs 21.6%, p = 05). The local MCR is consistently lower than the nominal MCRs (23.2% vs 30.2%, p < 0.001); however, the difference between the mean and local MCRs is small (23.9% vs 23.2%). Conclusions An expectation that a PED can achieve a MCR of 30% may not be reasonable. Device oversize and deformation during deployment lower the local MCR by 5–7%. A lowered MCR affects the aneurysm occlusion rate at six months.